2018
DOI: 10.1590/0100-29452017607
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Cowpea aphid-borne mosaic virus in in vitro germinated genotypes of Passiflora setacea

Abstract: Passion fruit (Passiflora edulis) is a fruit species of great relevance for Brazilian economy. However, it is highly susceptible to the Cowpea aphid-borne mosaic virus (CABMV). The species P.setacea, on the other hand, is resistant to the disease. The present study aimed to identify CABMV-resistant P. setacea genotypes for the introgression of genes into sour passion fruit genetic breeding programs. The seeds of passion fruit genotypes were germinated in vitro in MS culture medium. The seedlings were acclimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
6
0
2
Order By: Relevance
“…This is due to the fact that group III contains the genotypes of the recurrent parent (P. edulis), known for being highly susceptible to CABMV. Passiflora setacea, in turn, allocated from group I, has a higher level of resistance to CABMV, which can be seen in other studies developed by our research group (Santos et al 2015 b;Freitas et al 2015;Santos et al 2017). The AUDPC is used to evaluate the severity of the woodiness virus, and it has shown to be efficient in identifying susceptible genotypes with levels of resistance to the virus in other works involving passion fruit (Santos et al 2015 b), P. setacea, and segregating populations (Santos et al 2015 b;Freitas et al 2015).…”
Section: Groupssupporting
confidence: 85%
See 1 more Smart Citation
“…This is due to the fact that group III contains the genotypes of the recurrent parent (P. edulis), known for being highly susceptible to CABMV. Passiflora setacea, in turn, allocated from group I, has a higher level of resistance to CABMV, which can be seen in other studies developed by our research group (Santos et al 2015 b;Freitas et al 2015;Santos et al 2017). The AUDPC is used to evaluate the severity of the woodiness virus, and it has shown to be efficient in identifying susceptible genotypes with levels of resistance to the virus in other works involving passion fruit (Santos et al 2015 b), P. setacea, and segregating populations (Santos et al 2015 b;Freitas et al 2015).…”
Section: Groupssupporting
confidence: 85%
“…The periods of harvest, evaluation of fruits, and evaluation of the vegetative and floral morphological traits occurred throughout the entire year of 2016 until the first quarter of 2017. P. edulis (susceptible to CABMV) x P. setacea (resistant) Proteomic Interspecific Hybrids Phenotyping Estimates od genetic parameters Freitas et al, 2016) Evaluation of resistance to CABMV Freitas et al, 2015) Best-performing hybrids H5-14; H5-1; H2-10; H1-15L H5-16 H5-13 (donors)…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…With this in mind, genotypes that presented mild symptoms (DI from 4.19 to 15.75%) should be considered for selection aiming resistance to CABMV from interspeci c hybridization. Previous studies reported resistance to CABMV in genotypes belonging to P. setacea [22,48], P. cincinnata [22,24], P. gibertii [24] and immunity in P. suberosa [21]. This research is pioneer in reporting immunity to CABMV in P. bahiensis and P. pohlii and moderately resistant in P. miersii, amplifying the number of wild species of Passi ora spp.…”
Section: Discussionmentioning
confidence: 84%
“…Subsequently linear regression calculation was applied regarding the Cycle threshold variables (Ct) vs. Log of cDNA concentrations (ng.µL -1 ) to determine the correlation coe cient (R 2 ) among the points of each dilution and the curve inclination (Slope) [39]. The concentration of the number of copies of CABMV (copies.μL -1) in each point of the serial dilution was determined with application of the following formula: Copy Numbers (CN.µL -1 ) = (Sample concentration [ng] x 6.022x10 23 )/(fragment size [pb] x 1x10 9 x g/mol) [ 40 41].…”
Section: Standard Curve Of the Real-time Pcr Essay (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation